Comparative Study of Manual and SCADA-Based Water Treatment Processes with Operator Competency as a Moderating Variable - R. Sri Rezeki Karuniawangsih; Bambang Soenarto (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
This study evaluates the comparative operational performance of manual and Supervisory Control and Data Acquisition (SCADA)-based water treatment systems and examines the moderating role of operator competency. A quantitative comparative design was applied to operational data from two water treatment facilities of Perumda Tirta Bhagasasi Bekasi and a survey of 150 personnel involved in production activities. Electricity and chemical consumption were compared using operational records, while the relationships among manual treatment, SCADA implementation, operator competency, and operational performance were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The operational records showed that the SCADA-based facility required lower electricity and chemical inputs than the manual facility during the observed period. The measurement model demonstrated acceptable indicator validity and construct reliability. The structural model produced an R² of 0.768 and Q² of 0.150, indicating substantial explanatory power and predictive relevance. SCADA implementation showed the strongest direct relationship with operational performance, while the interaction between SCADA and operator competency indicated that operator competency strengthens the contribution of digital process control. The findings demonstrate that technological automation should be implemented together with continuous operator competency development to achieve reliable, efficient, and sustainable water treatment operations.